Performance efficiency assessment of Vietnamese ports: An application of Delphi with Kamet principles and DEA model - Nhu-Mai Thi Nong (Asian Journal of Shipping and Logistics (AJSL), 2023)
Ports form important links in the overall trade chain and act as driving forces for marine economic development. However, the operation of ports also has certain difficulties and challenges that port operators need to overcome. As such, this research aims to measure the performance efficiency of 22 ports listed in the stock market in Vietnam - a developing country with notable progress and role in global seaborne transport. The hybrid method of Delphi technique with KAMET principle and input and output - oriented DEA method was applied to solve the problem of efficiency assessment. The Delphi technique with KAMET principle was used to determine the efficiency evaluation criteria whilst the input and output - oriented DEA was employed to measure the efficiency. The findings show that capital, operation expenses, labour, port area, quay length, depth, revenue, and cargo throughputs are considered as input and output variables in the port efficiency evaluation. Additionally, it is also concluded in the research that scale and management skills are the dominant source of efficiency and Vietnamese ports show rather high management skills. Moreover, comprehensive and multi-variable assessment of port system may bring lots of benefits not only to the decision-making units but also the maritime authorities within constraint funds.
Keywords: C44; L91; R42; 650; DEA; Delphi; KAMET; Performance efficiency; Port